(untitled) (CIPEEX, 2025)
The aim of this study was to evaluate the influence of cusp coverage on the stresses and deformations of molars using the three-dimensional finite element method. For this purpose, two models were created, with and without cusp coverage (overlay or inlay). Using CAD, which is a three-dimensional graphic design program (SolidWorks 2018), a prototype of a lower human molar was constructed and restored with both approaches. The two models were exported to specific finite element analysis software (Ansys Workbench) and mechanical properties, meshing, boundary conditions, and loading were added. A static oblique occlusal load (30º) of 131.9 N was applied to the buccal grinding slope of the tooth, simulating displacement to reproduce the chewing function. The analysis was performed quantitatively and qualitatively with the variables of maximum principal stress (tension), maximum shear stress, and maximum displacement for both the reconstructions and the remaining tooth.